Carvacrol attenuates N-nitrosodiethylamine induced liver injury in experimental Wistar rats - Balan Rajan; Rajendran Ravikumar; Thandavamoorthy Premkumar; Thiruvengadam Devaki (Food Science and Human Wellness)
Carvacrol is a main constituent in the essential oils of countless aromatic plants including Origanum Vulgare and Thymus vulgari, which has been assessed for substantial pharmacological properties. In recent years, notable research has been embarked on to establish the biological actions of Carvacrol for its promising use in clinical applications. The present study is an attempt to reveal the protective role of Carvacrol against N-Nitrosodiethylamine (DEN) induced hepatic injury in male Wistar albino rats. DEN is an egregious toxin, present in numerous environmental factors, which enhances chemical driven liver damage by inducing oxidative stress and cellular injury. Administration of DEN (200 mg/kg bodyweight, I.P) to rats results in elevated marker enzymes (in both serum and tissue). Carvacrol (15 mg/kg body weight) suppressed the elevation of marker enzymes (in both serum and tissue) and augmented the antioxidants levels. The hoisted activities of Phase I enzymes and inferior activities of Phase II enzymes were observed in DEN-administered animals, whereas Carvacrol treated animals showed improved near normal activity. Histological observations also support the protective role of Carvacrol against DEN induced liver damage. Final outcome from our findings intimate that Carvacrol might be beneficial in attenuating toxin induced liver damage.